Penerapan Metode Time Line Dalam Pembelajaran PAI di SMA N 1 Tanjung Mutiara - Yetriyanti Yetriyanti; Charles Charles; Arifmiboy Arifmiboy; Afrinaldi Afrinaldi (Pusat Riset dan Inovasi Nasional, 2023)
The background of this research is that some students have a low level of awareness in participating in PAI learning activities, especially about historical material. Students are less enthusiastic in participating in learning and students are less involved in the process of teaching and learning activities. From the problems that exist, researchers are interested in examining the application of the time line method in PAI learning at SMAN 1 Tanjung Mutiara and its inhibiting factors. This study aims to find out how the application of the Time line learning method and its inhibiting factors. This type of research is descriptive qualitative research which describes the application of the time line method in PAI learning at SMAN 1 Tanjung Mutiara. In collecting data researchers used observation techniques, interviews and documentation. Meanwhile, to analyze it, the researcher uses data reduction, data presentation and conclusion drawing. Researchers checked the data that had been obtained from various research instruments, namely teachers, principals and students using source triangulation, researcher triangulation and method triangulation. So as to produce a credible conclusion. From the research that has been done, it can be concluded that the application of the time line method in PAI learning at SMAN 1 Tanjung Mutiara starts with teacher planning in preparing lessons by making lesson plans which serve as teacher guidelines in teaching and learning activities carried out in the classroom. The application of the Time Line method in learning is carried out through three activities, namely preliminary activities, core activities and closing activities. The essence of applying the time line method is that students observe, analyze and discover for themselves related to learning in discussion activities. The inhibiting factors found were the short time allocation, the teacher's ability to link learning, students playing around during discussions, and female students being more active than male students.